The association between family health and depression and anxiety symptoms among older adults: a cross-sectional study in mainland China - Ma, Sha (BMC public health, 2025)
Background There was a scarcity of literature examining the relationship between family health and depressive and anxiety symptoms among older adults. This study aims to investigate the association of family health and mental health outcomes (specifically depressive and anxiety symptoms in the Chinese older adult population, while concurrently developing novel intervention strategies and methodological approaches to address mental health challenges within this vulnerable demographic. Methods Chi-square tests and multinomial logistic regression were employed to examine both univariate and multi-univariate associations between family health and depressive and anxiety symptoms among older adults. Additionally, Cronbach’s alpha and Kaiser-Meyer-Olkin measure were employed to evaluate the reliability and validity of the scales used in this study. Results This study encompassed a total of 1147 respondents aged 60 years and above, comprising of 49.35% female and 50.65% male participants. Univariate analysis indicated that elevated prevalences of depressive and anxiety symptoms were significantly associated with multiple factors, including insufficient formal education, a monthly income below CNY1500, living alone, absence of a marital relationship, elevated stress levels, compromised family health conditions, and inadequate perceived social support. Multinomial logistic regression analysis demonstrated that family health, perceived social support, chronic disease status, marital status, physical activity, and educational attainment consistently exerted significant influences on the prevalence of depressive and anxiety symptoms among older adults. Conclusions Priority should be placed on family-centered health promotion strategies aimed at mitigating depressive and anxiety symptoms.